Pyrazole synthesis under microwave irradiation and solvent-free conditions - Buriol,Lilian (2010)
This paper presents a study of solvent-free reaction conditions using microwave irradiation (MW) to obtain 4,5-dihydro-1H-pyrazoles and dehydrated pyrazoles by the cyclocondensation reaction of 4-alkoxy-1,1,1-trifluoro-3-alken-2-ones [CF3C(O)CH=C(R¹)OR, where R/R¹ = Et/H, Me/Me and Me/Ph] with hydrazines [NH2NH-R², where R² = CO2Me, Ph, CH2CH2OH]. Some reactions were performed under the same reaction conditions using methanol as solvent. The results obtained using MW equipment for synthesis under solvent-free conditions were also compared with those described in literature for conventional thermal heating and heating with a domestic MW oven. In general, the products furnished by reaction in MW equipment for synthesis presented better yields and shorter reaction times. In addition, it was demonstrated that the reaction temperature altered the formation of products for each hydrazine showing that MW equipment for synthesis is efficient for reacting hydrazines and 4-alkoxy-1,1,1-trifluoro-3-alken-2-ones to procedure the products 4,5-dihydro-1H-pyrazoles and dehydrated pyrazoles.